The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/ijn.12987
|View full text |Cite
|
Sign up to set email alerts
|

Self‐care activities among patients with type 2 diabetes mellitus: A cross‐sectional study

Abstract: Aims This study investigated self‐care activities and identified their related factors in Chinese patients with type 2 diabetes mellitus. Methods A cross‐sectional study was conducted in Guangzhou, China, between September 2016 and February 2017, involving 202 Chinese patients with type 2 diabetes mellitus. Measures included the Summary of Diabetes Self‐Care Activities Questionnaire and Revised Illness Perception Questionnaire. Results Self‐care activities in Chinese patients with type 2 diabetes mellitus were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…As the income level of households increased, it was noted that selfcare behaviors were significantly reduced and HbA1c levels were increased. Most of the previous studies reported significant differences among self-care behaviors, HbA1c status, and sociodemographic factors among patients with type 2 diabetes (29)(30)(31)(32)(33)(34)(35)(36)(37). A study in Northern Jordan demonstrated that HbA1c level is significantly related to household income, education levels, employment status, and disease duration (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the income level of households increased, it was noted that selfcare behaviors were significantly reduced and HbA1c levels were increased. Most of the previous studies reported significant differences among self-care behaviors, HbA1c status, and sociodemographic factors among patients with type 2 diabetes (29)(30)(31)(32)(33)(34)(35)(36)(37). A study in Northern Jordan demonstrated that HbA1c level is significantly related to household income, education levels, employment status, and disease duration (16).…”
Section: Discussionmentioning
confidence: 99%
“…In studies, the observed diabetes-related knowledge and self-care knowledge were associated with self-care behaviors ( 38 , 42 ). Patients who have better knowledge about the symptoms of diabetes are more successful in testing their blood sugar and exercising ( 34 , 44 ). Knowledge, attitudes, and behaviors to promote health-related behaviors and prevent diseases are related ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The late diagnosis may partially contribute to the high prevalence of DKD in Asia and Africa. In Asia, healthcare providers and nurses are not sufficiently educated about diabetes patients, about 50% lack understanding of diabetes complications,32 and self-care activities are suboptimal overall 33. Therefore, it is extremely significant to have an accurate prediction model that could assist clinicians in real-time evaluation of patient risk and implement primary and secondary preventive measures to delay progression of disease.…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese version of SDSCA has an acceptable internal consistency, with Cronbach’s α range from 0.62 to 0.98. 30 …”
Section: Methodsmentioning
confidence: 99%
“…The Chinese version Open access of SDSCA has an acceptable internal consistency, with Cronbach's α range from 0.62 to 0.98. 30 The DES-SF measures the psychosocial empowerment of patients with diabetes. 31 The 8-item DES-SF employs the 5-point Likert scoring system.…”
Section: Measurementsmentioning
confidence: 99%